1998
DOI: 10.1099/00221287-144-2-391
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chitin synthesis during dimorphic growth of Candida albicans

Abstract: Candida albicans has three genes encoding chitin synthase enzymes. In wildtype strains, the expression of CHS2 and CHS3 peaked 1-2 h after the induction of hyphal growth, whilst mRNA levels in a non-germinative strain, CA2, remained low under the same conditions. CHSl gene expression did not peak during germ tube formation but remained a t low levels in both yeast and hyphal growth. The pattern of gene expression did not predict the changes in measured chitin synthase activities or changes in chitin content du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 57 publications
1
80
0
Order By: Relevance
“…Remarkably, the changes in the cell wall composition were demonstrated during hyphal growth as well. No increase in chitin level, which normally occurs in hyphal cell walls (Munro et al, 1998;Sullivan et al, 1983), was observed (Table 5). This is consistent with earlier observation of the inability of the pde2 null mutant to form normal hyphae in liquid media in response to serum and, indeed, to other hyphal inducers (Jung and Stateva, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Remarkably, the changes in the cell wall composition were demonstrated during hyphal growth as well. No increase in chitin level, which normally occurs in hyphal cell walls (Munro et al, 1998;Sullivan et al, 1983), was observed (Table 5). This is consistent with earlier observation of the inability of the pde2 null mutant to form normal hyphae in liquid media in response to serum and, indeed, to other hyphal inducers (Jung and Stateva, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we used time lapse video-microscopy to determine whether inhibition of different classes of chitin synthase affected the localization of Chs3-YFP. RO-09-3143 was used to inhibit Chs1, and nikkomycin Z to preferentially inhibit the class I enzymes, Chs2 and Chs8 (Gaughran et al, 1994;Munro and Gow, 1995;Munro et al, 1998). …”
Section: Morphogenesis Of C Albicans Salvage Septamentioning
confidence: 99%
“…Null mutants lacking Chs3 are viable but have very low cell wall chitin contents (Bulawa et al, 1995). Chs2 and Chs8 account for .90% of in vitro chitin synthase activity (Gow et al, 1994;Munro et al, 1998;Munro et al, 2003), are normally non-essential, but are strongly upregulated in response to cell wall stress such as treatment with echinocandin antifungals Walker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chitin synthase activity was determined in MMF of C. albicans cells by the method of Munro et al 17 The MMFs were activated by 5-min incubation with 100 ng trypsin μl −1 MMF at 30°C and the reactions were stopped by addition of 150 ng soybean trypsin inhibitor μl range). Incubations were carried out at 30°C for 30 min and the reaction was stopped by addition of 1 ml of 66% (v/v) ethanol.…”
Section: Determination Of Chitin Synthase Activity and Measurement Ofmentioning
confidence: 99%